[Article Retracted] WACANA PAHAM KEAGAMAAN TV ONE DAN METRO TV DALAM PEMBERITAAN DEMO 411 DI JAKARTA - Mustain Mustain (Jurnal Penelitian Agama, 2017)
This article is retracted, because it has been published in KOMUNIKA: Journal of Da'wah and Communication volume 11 number 2 of 2017. To read the full text of this article please visit http://ejournal.iainpurwokerto.ac.id/index.php/komunika/article/view /1364 with a DOI number https://doi.org/10.24090/komunika.v11i2.1364. Thus the statement of retraction is made to make sense of it. Abstract: This research is a qualitative research, using discourse analysis method of Teun Van Dijk. The news is the 6th issue with three details sourced from Tv One and 3 from Metro Tv. Discourse analysis in this case is used as a tool to see the discourse delivered by Metro Tv and Tv One in preaching peace action 411. There are three stages of text analysis, cognition analysis, and social analysis. The results showed that Tv One in preaching peace action 411 discourse that the Muslims who perform such acts as tolerant Muslims, maintaining unity and running the shari'ah of Islam, while Metro TV in preaching peace action 411 menyebanakan that Muslims who take peaceful action is a group of ideology hardline, anti-tolerance and likes to use violence. Keywords: Peace Action 411, Metro Tv, Tv One, Exclusive Islam, Inclusive Islam